Determinan Cash Holding pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Mariana Mariana; Azharsyah Ibrahim (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2022)
Study on cash holding has attracted our attention due to a common activity of companies in holding the cash in a relatively high amount. In long term, this activity will negatively affect the businesses financial performance. This study intends to examine the effect of capital expenditure and dividend payments on cash holding of manufacturing companies listed on the Indonesia Stock Exchange in 2012-2017. It employs data panels using 29 samples with 174 observations. The findings show that capital expenditure and dividend payments have a positive significant impact on cash holding of the manufacturing companies that listed in Indonesian Stock Exchange in the said period, when examined both simultaneously and partially. It means that the policy of capital expenditure and dividend payments affect the amount of cash holding in the listed manufacturing companies.